Price Improvement and Execution Risk in Lit and Dark Markets - Brolley, Michael (Management Science, 2020)
Dark pools offer price improvement over displayed quotes, but nondisplayed liquidity implies execution uncertainty. Because investor limit orders also provide price improvement with execution risk, dark pools offer a natural substitute. In a model of informed trading in a market with a displayed limit order book and a dark pool that offers price improvement, higher valuation investors sort into order types with lower execution risk, generating an “immediacy hierarchy.” Dark pool price improvement predicts the order in the hierarchy: a price improvement closer to (farther from) the midquote positions dark orders below (above) limit orders, which improves (worsens) market quality and welfare. A dark pool that is operated by the limit order book is welfare improving, and welfare reduces with an independently operated pool. Because active and passive order flow migrate to the dark pool where price impact occurs only post-trade, price efficiency worsens with any positive level of dark trading. This paper was accepted by Gustavo Manso, finance.